2008
DOI: 10.1007/s00436-008-1123-0
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the immune response to coccidiosis on the age of rabbit suckling

Abstract: To study the immune response to coccidiosis, the suckling rabbits were inoculated with 2,000 oocysts of either Eimeria intestinalis or Eimeria flavescens at 19, 22, 25, 29, and 33 days of age (DA) and in the case of E. intestinalis at 14 and 16 DA as well and sacrificed 14 days later. Another group served as an uninfected control and the rabbits were killed at the same age as their infected counterparts. Unlike the antibody response, the parameters reflecting cellular immunity (total number of leukocytes in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
2
28
1
2
Order By: Relevance
“…Despite good cage sanitation, fecal coccidian oocyst loads from majority of the farms were unsatisfactory (>1000 OPG). This was in contrary to the findings by Gonz alez-Redondo et al (2008) and Pakandl et al (2008) that good farm hygiene is sufficient to maintain low coccidian levels on a farm.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Despite good cage sanitation, fecal coccidian oocyst loads from majority of the farms were unsatisfactory (>1000 OPG). This was in contrary to the findings by Gonz alez-Redondo et al (2008) and Pakandl et al (2008) that good farm hygiene is sufficient to maintain low coccidian levels on a farm.…”
Section: Discussioncontrasting
confidence: 56%
“…First, na€ ıve rabbits are more susceptible to infection from adult carriers especially after weaning (Pakandl et al 2008;Papeschi et al 2013) and since most rabbit keepers in Kenya (50.8%) mainly housed their rabbits in groups, housing and husbandry practices are likely risk factors. Second, weaning stress has been reported to lower immunity of rabbits to infection (Papeschi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study (Pakandl et al 2008; Papeschi et al 2013) showed that the number of oocysts shedding in feces is correlated to the intensity of invasion, age, and immune status of animals. Oocyst shedding pattern also depends on sex and physiological condition.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, mean oocyst number registered in the juvenile period of examined animals was significantly higher compared to those observed after the 2 parturitions. This may depend on the incomplete maturity of the immune system of kits and/or of the lack of a protective immune response deriving from previous infections (Gomez-Bautista et al, 1987;Grès et al, 2003;Gutierrez, 2003;Pakandl et al, 2008). Indeed, in rabbits the development of an acquired resistance to Eimeria infections appears at about 3 mo of age (Gomez-Bautista et al, 1987).…”
Section: Discussionmentioning
confidence: 99%